2007
DOI: 10.1115/1.2737476
|View full text |Cite
|
Sign up to set email alerts
|

Spray Cooling of High Aspect Ratio Open Microchannels

Abstract: Direct spraying of dielectric liquids has been shown to be an effective method of cooling high-power electronics. Recent studies have illustrated that even higher heat transfer can be obtained by adding extended structures, particularly straight fins, to the heated surface. In the current work, spray cooling of high-aspect-ratio open microchannels was explored, which substantially increases the total surface area and allows more residence time for the incoming liquid to be heated by the wall. Five such heat si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The temperature gradients near the contact line on a smooth surface were examined using thermochromic liquid crystals and were proven to be larger than those in other areas, making the hypothesis reasonable. Their results validated and extended the triple contact line length enhancement mechanism proposed by Horacek et al [115,116]. In their following research, it was found that the substrate temperature and heat flux distributions had a local minimum and a local maximum beneath the three-phase contact line, respectively, which is resulted from strong local evaporation.…”
Section: Mems-based Microstructures and Otherssupporting
confidence: 75%
“…The temperature gradients near the contact line on a smooth surface were examined using thermochromic liquid crystals and were proven to be larger than those in other areas, making the hypothesis reasonable. Their results validated and extended the triple contact line length enhancement mechanism proposed by Horacek et al [115,116]. In their following research, it was found that the substrate temperature and heat flux distributions had a local minimum and a local maximum beneath the three-phase contact line, respectively, which is resulted from strong local evaporation.…”
Section: Mems-based Microstructures and Otherssupporting
confidence: 75%
“…Thermal management of the switches has become a primary design goal in the packaging of power converters. Many aggressive cooling methods, such as jet cooling, spray cooling, and two-phase cooling, have been and are being developed which are capable of handling heat fluxes above 100 W/cm 2 , with some capable of dissipating near or above 1 kW/cm 2 [1][2][3][4][5]. However, such cooling methods usually involve additional complexity and lack sufficient understanding of the fundamental physics of liquid-vapor flow interaction, making accurate and reliable analysis and design optimization more difficult [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, temperature influences the molecular arrangement of droplets and can be used to change the wettability of a substrate [18,21]. Nanodroplets are relevant to many processes that occur at high temperatures such as physical vapor deposition and spray-cooling [22]. In this work, droplets were simulated at the boiling temperature (373 K) of water and at room temperature which enabled the influence of temperature to be investigated in relation to droplet sizes and impingement velocities of the droplet.…”
Section: Introductionmentioning
confidence: 99%